Response of some tropical nitrogenfixing woody legumes to drought and inoculation with mycorrhiza - Awotoye, O.O.; Atayese, M.O.; Osonubi, O.; Mulongoy, K.; Okali, D.U.U. (1992)
This paper reports on a study of the influence ofdrought and inoculation with mycorrhiza on dry-matter production, nutrient uptake and water relations of Acacia auriculiformis, Albizia lebheck. Gliricidia sepium and Leucaena leucocephala in a sterile soil. Inoculation with L. leucocephala roots containing vesicular-arbuscular mycorrhizal (VAM) fungi (Glomus and Acaulospora spp.) resulted in infection of 25-68% in regularly watered plants. Drought stress reduced infection by 8-49%. In general, VAM plants survived better, and had more dry matter and nutrients and a larger leaf area, than uninoculated plants. For A. auriculiformis. however, the VAM inoculant reduced leaf area, plant dry weight and nitrogen content, although it increased phosphorus uptake. Inoculation ofA . auriculiformis with the ectomycorrhizal fungus Boletus suillus resulted in higher nutrient uptake than in non-mycorrhizal and VAM plants. Drought stress tended to reduce plant growth as well as phosphorus and nitrogen uptake. With the exception of A. auriculiformis, nutrient content in drought-stressed VAM plants was either greater than or comparable with the nutrient content of unstressed non-mycorrhizal plants.